Facilitating screening of Klinefelter syndrome among patients with diabetes. Issue 2 (7th August 2019) - Seno, Yohei; Iwasaki, Yorihiro; Aizawa‐Abe, Megumi; Iwasaki, Kanako; Yoshiji, Satoshi; Honjo, Sachiko; Hamasaki, Akihiro
Abstract : Klinefelter syndrome (KS) is frequently complicated by diabetes. However, it is severely underdiagnosed due to a lack of reliable screening methods. We diagnosed two patients with KS at the Center for Diabetes and Endocrinology, Tazuke Kofukai Medical Research Institute Kitano Hospital, Osaka, Japan. By comparing the patients with 39 non‐KS patients with diabetes, we propose a screening tool for KS in patients with diabetes.